Hello :
the general term is :
an = a1+(n-1)×d
or : an = ap +(n-p)×d......d is common diffrence
let : n=10 and p= 4
a10 = a4 +(10-4)×d
64 = 22 + 6d
6d = 42
d= 7
conclusion :
a4 = 22
a3 = 22-7=15
a2=15-7=8
a1= 8-7=1
<span>the first five terms : 1 , 8 , 15 , 22</span>
The first step for solving this expression is to reduce the fraction with 11.

Now reduce the fraction with

.

Reduce the fraction one more time with

.

To take the root of a fraction,, we must take the root of the numerator and denominator separately. This rule will change the expression to the following:

Since we cannot simplify this fraction any further,, the final answer is going to be

.
Let me know if you have any further questions.
:)
Answer: X = 1/4 or X = -1
Step-by-step explanation:
4x2+3x−1=0
(4x−1)(x+1)=0
4x−1=0 or x+1=0
4x=1 or x=-1
Now divide 4 from both sides
like this 4x/4=1/4
now cancel out two 4's so the answer will be x=1/4
Answer:
8.27837797
I think this is correct im not completely sure.